Impact of poaching on an Asian elephant population in Periyar, southern India: a model of demography and tusk harvest - R. Sukumar, Uma Ramakrishnan and J. A. Santosh (Animal Conservation (1998) 1, 281-291, 1998)
Ivory poaching has been a serious problem in Asian elephant (Elephas maximus) populations. Reliable records of elephants killed and ivory harvested are generally unavailable. We have used a simulation modelling approach to estimate the numbers of male elephants killed and the quantities of ivory harvested over a 20 year period (1974-94) in the Periyar Reserve of southern India. The age-structured Leslie matrix projection model was modified for this purpose by considering three segments (female, tusked male and tuskless male), relating fecundity to adult sex ratio and iteratively simulating tusked male mortality rates so as to match the observed elephant population structure at Periyar. Four different scenarios of poaching all gave very similar results. We estimate conservatively that 336-388 tuskers have been poached and 3256-3334 kg of ivory harvested by poachers over the 20 year period. The maximum harvest came from the 10-20 year age class. Trends in various demographic parameters such as population numbers, tusked male to tuskless male ratios and female fecundity are described. The implications of ivory poaching and the extremely skewed sex ratios for the conservation and management of the elephant population at Periyar are discussed